Orbital presentation of systemic vasculitis: a diagnostic and management challenge - Singh, M; Singh, U; Zadeng, Z (Nepalese Journal of Ophthalmology, 2015)
Background: Orbital involvement in Wegener’s Granulomatosis (WG) is rare and has an overall good prognosis. Case: A 60-year-old hypertensive Indian female presented with vision loss and painful proptosis of left eye. Orbital incisional biopsy suggested necrotising small vessel inflammation. The saddle nose deformity and pedal nodulo- ulcerative lesions further consolidated the diagnosis of Wegener’s granulomatosis. Systemic immunosuppressant provided remission and the only relapse was managed successfully with intravenous Rituximab. Conclusion: Wegener’s granulomatosis should be kept in the differential diagnosis of painful proptosis with a diffuse orbital mass in an elderly patient presenting with profound vision loss. Newer immune modulating agents are useful adjuncts in preventing relapses of this fatal disease.